Zircon U-Pb age geochemical constraints on the origin and tectonic implication of late cretaceous arc-type magmatism in Pertek region (Tunceli, East Turkey) - Sar, Abdullah; Bingöl, Ahmet Feyzi; Ertürk, Mehmet Ali; Rizeli, Mustafa Eren (My University, 2018)
The plutonic units of the Elazıg Magmatics crop out in the Pertek-Tunceli (Turkey) region in the Southeast Anatolian Orogenic Belt. This study reports geochemical data, Sr-Nd isotope ratios and U-Pb zircon age of the Late Cretaceous granitoids. Granitoids belonging to Elazıg Magmatics consist of tonalite, granodiorite, monzogranite, gabbro, diorite, monzodiorite and quartz monzodiorite. Geochemically, they have SiO2=45.56-76.03%, MgO=0.07-8.99%, Mg# =8.7- 75.4 and Al2O3=12.19-23.76%. Geochemical analyzes suggest that granitoids are peralüminous and I type and vary from low-K tholeiitic to shoshonitic in composition. The result of LA-ICP-MS U-Pb zircon dating revealed that these granitoids formed, in the Late Cretaceous (77.2±1.1-80.6±0.9 Ma). Trace element patterns normalized primitive mantle and chondrite normalized REE indicate that in LREE relating to HREE and in LILE relating to HFSE have enrichments. (87Sr/86Sr)i values of these rocks vary between 0.7039 and 0.7072 in the compositions. On the other hand, ?Ndi is between -1.7 and 6.7. Therefore, the variation is indicative of changing in the source components in the Elazıg Magmatism that we attribute to tectonic switching from an intra-oceanic subduction setting to a collision with the Arabian continent in the region.
Bildiri - Yayımlanmış
Keywords: Intra oceanic subduction; Sr-Nd isotope; U-Pb dating; SE Turkey; Elazığ magmatics